2001
DOI: 10.1046/j.0962-1083.2001.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Prey specialization may influence patterns of gene flow in wolves of the Canadian Northwest

Abstract: This study characterizes population genetic structure among grey wolves (Canis lupus) in northwestern Canada, and discusses potential physical and biological determinants of this structure. Four hundred and ninety-one grey wolves, from nine regions in the Yukon, Northwest Territories and British Columbia, were genotyped using nine microsatellite loci. Results indicate that wolf gene flow is reduced significantly across the Mackenzie River, most likely due to the north-south migration patterns of the barren-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 49 publications
3
130
0
1
Order By: Relevance
“…It is possible that the two dingo populations have different ecological or biological characteristics relevant to the conservation and management of the species or its role in specific ecosystems. Patterns of genetic subdivision in other large carnivores have been linked to ecologically relevant characteristics such as neonatal dispersal (Sacks, Bannasch, Chomel, & Ernest, 2008; Sacks, Brown, & Ernest, 2004), prey specialization (Carmichael, Nagy, Larter, & Strobeck, 2001), environmental climes (Carmichael et al., 2001; Rueness, Jorde et al., 2003; Rueness, Stenseth et al., 2003; Stenseth et al., 2004), and sociality (Randall, Pollinger, Argaw, Macdonald, & Wayne, 2010). This is a key knowledge gap, which needs to be interrogated by future ecological research.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the two dingo populations have different ecological or biological characteristics relevant to the conservation and management of the species or its role in specific ecosystems. Patterns of genetic subdivision in other large carnivores have been linked to ecologically relevant characteristics such as neonatal dispersal (Sacks, Bannasch, Chomel, & Ernest, 2008; Sacks, Brown, & Ernest, 2004), prey specialization (Carmichael, Nagy, Larter, & Strobeck, 2001), environmental climes (Carmichael et al., 2001; Rueness, Jorde et al., 2003; Rueness, Stenseth et al., 2003; Stenseth et al., 2004), and sociality (Randall, Pollinger, Argaw, Macdonald, & Wayne, 2010). This is a key knowledge gap, which needs to be interrogated by future ecological research.…”
Section: Discussionmentioning
confidence: 99%
“…However, local-scale genetic structure can be detected in different regions of Europe (Pilot et al 2006;Aspi et al 2008;Czarnomska et al 2013) and elsewhere in the species distribution, and appears to be determined mainly by ecological features rather than geographical barriers (e.g. Carmichael et al 2001;Geffen et al 2004;Pilot et al 2006). Earlier genetic studies suggest that Bulgarian wolves contain high levels of genetic diversity compared to elsewhere in Europe (Lucchini et al 2004;Pilot et al 2006Pilot et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Pilot et al (2006) found that genetic differentiation in European wolves was correlated with climate, habitat types, and diet composition and also suggested that natalhabitat biased dispersal was the underlying mechanism linking population ecology vntin genetic sb:xicture. Apparently, in large canids, ecotypic divergence may be the primary mode of differentiation (Carmichael et al 2001;Musiani 2003;Geffen et al 2004;Sacks et al 2004Sacks et al , 2005Pilot et al 2006;Carmichael et al in press) presenting an alternative to topographically induced population structure (Avise 2000).…”
Section: Prey-mediated Differentiation Of Tundra/taiga and Boreal Conmentioning
confidence: 99%
“…Nonetheless, wolves vary geographically in size and coat colour and five or more subspecies co-exist in North America (Nowak 1995). Recently, genetic analysis of wolf populations separated by water barriers (Carmichael et al 2001) or existing in distinct habitats (Geffen etal. 2004;Pilot etal.…”
Section: Introductionmentioning
confidence: 99%